2023
DOI: 10.32604/jrm.2022.023795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Self-Healing Efficiency of Microcapsule-Based Self-Healing Cementitious Composites Based on Acoustic Emission

Abstract: Microcapsule self-healing technology is one of the effective methods to solve the durability problem of cementbased composites. The evaluation method of the self-healing efficiency of microcapsule self-healing cement-based composites is one of the difficulties that limits the self-healing technology. This paper attempts to characterize the self-healing efficiency of microcapsule self-healing cement-based composites by acoustic emission (AE) parameters, which provides a reference for the evaluation of microcaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It can effectively protect its internal substances from external interference. The microcapsules using melamine resin as the wall material were successfully synthesized and applied in coatings, demonstrating the feasibility of using microcapsules in coatings [13][14][15][16][17][18]. At the same time, the results also demonstrated that melamine resin as the wall material is prone to breakage when damaged.…”
Section: Introductionmentioning
confidence: 82%
“…It can effectively protect its internal substances from external interference. The microcapsules using melamine resin as the wall material were successfully synthesized and applied in coatings, demonstrating the feasibility of using microcapsules in coatings [13][14][15][16][17][18]. At the same time, the results also demonstrated that melamine resin as the wall material is prone to breakage when damaged.…”
Section: Introductionmentioning
confidence: 82%
“…However, the waterborne coatings will be damaged by external factors during use, resulting in microcracks [1][2][3][4][5][6]. Self-healing microcapsules can have a certain inhibitory effect on microcracks in waterborne coatings [7][8][9][10][11]. A melamine resin is nontoxic and odorless, with a simple preparation process and compact material, making it a good choice for microcapsule wall materials.…”
Section: Introductionmentioning
confidence: 99%